Localization of a Peripheral Residual Cyst: Diagnostic Role of CT Scan - Anshuman Jamdade; Gopakumar R. Nair; Madhur Kapoor; Neeta Sharma; Arya Kundendu (Hindawi Limited, 2012)
The term residual cyst is used most often for retained radicular cyst from teeth that has been removed. Residual cysts are among most common cysts of the jaws. The location of all odontogenic cysts is usually intraosseous. The peripheral (extraosseous) presentations are rare. The peripheral presentation of residual cyst has never been reported in the literature. In this article, the role of CT in diagnosing an unusual peripheral presentation of a residual cyst is discussed.